PROFIL DAN KARAKTERISTIK KLINIS PENGGUNAAN OBAT DISPEPSIA - Hasanah, Nur; Rahsa Puji, Lela kania; Maximus TulandI, Silvester; Putrajaya, Fadly; Kusmana, Indah (E-Jurnal Medika Udayana, 2022)
Dyspepsia is a syndrome with upper gastrointestinal pain, flatulence, epigastric/heartburn pain, early satiety, nausea, and vomiting. This study aims to determine the profile and characteristics of the use of dyspeptic drugs at Icon 8 BSD Clinic in 2021 based on age, gender, education, occupation, clinical manifestations, drug class, and variations for antiulcer medicines, dosage forms, and drug administration routes. This study is a descriptive study with a retrospective data evaluation; the data obtained from the medical records of dyspeptic patients using the probability sampling method is then presented as percentages and tables. The results showed that dyspepsia patients were dominated by the age range of 26-45 years (43.2%), female gender (51.9%), college education (41.4%), and having a job as an employee (33.3%). The most common clinical characteristic of dyspeptic patients was nausea (72.2%). Based on the H2 antagonist drug class, ranitidine (20.4%), with a combination of 2 antiulcer drugs, namely omeprazole and ranitidine (15.4%), tablet dosage form (70.9%) and oral route of administration (96.6% ).